Social Loafing pada Anggota Organisasi Mahasiswa Fakultas Psikologi UMS - Wildanto, Eri, Dr. Wiwien Dinar Pratisti, M.Si (2016)
Organizational activities have several working programs which have to be managed during the term. Then, in the beginning of the term tasks are distributed to all members. The enforcement of the tasks is a responsibility that has to be carried by each individual as a consequence of their status as members. The aim of this research is to understand and describe social loafing on members of student organizations in the Faculty of Psychology UMS. The data collection method is using open questionnaire. Informants involved in this research are 100 activists who are incorporated in student organizations' activities. The result of the research exhibits the forms of social loafing which are demonstrated by the members of student organizations in the Faculty of Psychology UMS are the members are not enforcing the tasks given, not running the working program in the organization, not willing to try new task besides the ones which are usually done, and never contribute ideas/aspirations in the organization. The background reasons of why the members of the student organization doing social loafing can be divided in to two, the first are internal problems happening in the organization including no respect to each and everyone in the organization, different opinion towards one another, the lack of operational budget, lack of coordination and communication on enforcing a task, and no supportive atmosphere within the organization. Second reasons are individual problem within each member to contribute including the lack of time management, lack of self-confidence, the feeling of less knowing other members and the members do not understand well about the tasks given.